2017
DOI: 10.3390/su9060881
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumers’ Intentions to Participate in a Formal E-Waste Collection System: A Case Study of Onitsha, Nigeria

Abstract: Due to the increasing amount of electronic waste (e-waste) generated in Nigeria, challenges such as consumer disposal behaviors have emerged. An understanding of consumers' intentions to participate in formal e-waste collections is key in increasing the level of participation in an e-waste collection scheme. The theory of planned behavior (TPB) creates an applicable platform for identifying the determinants of recycling intention. Based on the TPB, we develop a theoretical framework to study how influencing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 40 publications
10
70
0
2
Order By: Relevance
“…Based on TPB, users' adoption of mobile money is explained by their intentions [15,32]. The intentions are a function of subjective norms, attitude and perceived behavioral control [30,33].…”
Section: Mobile Money Adoption In East Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Based on TPB, users' adoption of mobile money is explained by their intentions [15,32]. The intentions are a function of subjective norms, attitude and perceived behavioral control [30,33].…”
Section: Mobile Money Adoption In East Africamentioning
confidence: 99%
“…As recommended by Nduneseokwu et al [32], we determine the sample size for an infinite population at Z = 1.96 and 95% confidence level, which results in 384 as sample size. Nduneseokwu et al [32] further suggested an adjustment to the population (1,578,133) of Kampala city, to obtain an adjusted population size by using the following formula:…”
Section: Design Of the Study And Sampling Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ajzen's [17] Theory of Planned Behaviour (TPB) is a widely used framework for studying environmental behaviour, including recycling [18][19][20][21]. According to the TPB, three factors (independent constructs) guide human behaviour (the dependent construct), including 'attitude' towards a certain behaviour (i.e., beliefs about the consequences of performing the behaviour), 'subjective norm' (i.e., perception of others' expectations of one to perform the behaviour, notably social pressure), and 'perceived behavioural control' (PBC) (i.e., how much control one believes one has to perform the behaviour, notably the ability to perform the behaviour).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We used Ajzen's [24] well-known Theory of Planned Behaviour (TPB) as a theoretical framework considering its applicability to environmental behaviour, especially recycling [25][26][27][28]. According to the TPB, there are three determinants of behaviour, including 'attitude' towards the behaviour (i.e., perceptions about the consequences of performing the behaviour), 'subjective norm' (i.e., perceptions of others' expectations to perform the behaviour, notably social pressure), and 'perceived behavioural control' (PBC) (i.e., perceptions of how much control one has to perform the behaviour, notably the ability to perform the behaviour).…”
Section: Theoretical Frameworkmentioning
confidence: 99%